Lie Groups and Quantum Chromodynamics - Davey, Aaron C.H. (MacEwan University Student eJournal, 2020)
This article explores the mathematics of group theory, in particular Lie groups and their representations, and its connection to quantum field theory, specifically quantum chromodynamics. The first half discusses specific Lie groups and their Lie algebras and uses this information to describe the theory of the strong force, its particle constituents and a property of subatomic particles known as colour charge. This article emphasizes the importance of utilizing abstract algebra for the continued advancement of quantum physics in the modern era.